Challenges and Prospects of the National Health Insurance Scheme and Medical Service Delivery in The Nigerian Navy. (International Journal of Scientific Research and Management (IJSRM), 2023)
Background: The National Health Insurance Scheme (NHIS) was introduced into the Nigerian Navy (NN) in December 2006. It was meant to provide the alternative funding and technical imputes needed to revive the ailing medical service delivery in the NN. However, 5 years after the implementation of the Scheme, there are still problem of ‘out of stock syndrome’ of drugs while the quality of medical service delivery is still sub optimal. Hence, many NN personnel prefer to seek healthcare outside the Nigerian Navy Medical Service (NNMS). The aim of this study was to investigate the contributions of NHIS to medical service delivery in the NN, also to find out the challenges and prospects for optimizing the implementation of NHIS for enhanced medical service delivery in the NN. Method: This study was a descriptive survey research. Primary data was collected using questionnaire and consultations. Secondary data was collected from books, official documents and publications, journals, internet, published and unpublished material. The data collected were analyzed and expressed as frequencies and percentages and thereafter presented in tables. Results: The research findings showed a statistically significant relationship between NHIS and medical services delivery in the NN. It also revealed that the NHIS has contributed to the improvement of the NN medical service delivery. However, inadequate staffing, inadequate and obsolete medical equipment were found as challenges to optimal implementation of the Scheme for enhancing medical service delivery in the NN. Other challenges include poor attitude of medical personnel, insincerity in management of NHIS and exclusion of operational/occupational injuries. Conclusion: In conclusion the study was able to establish a significant relationship between NHIS and medical services delivery in the NN. It also ascertained the various contributions of NHIS to medical service delivery in the NN. The study identified significant improvement in the quality of medical service delivery in the NN within the 5 years of implementation of the Scheme.